2015
DOI: 10.1021/cs501962m
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Catalysis in Oxidation of Hydrocarbons with Ozone in Acetonitrile

Abstract: Oxidation of alcohols, ethers, and sulfoxides by ozone in acetonitrile is catalyzed by sub-millimolar concentrations of Fe(CH 3 CN) 6 2+ . The catalyst provides both rate acceleration and greater selectivity toward the less oxidized products. For example, Fe(CH 3 CN) 6 2+ -catalyzed oxidation of benzyl alcohol yields benzaldehyde almost exclusively (>95%) whereas uncatalyzed reaction generates a 1:1 mixture of benzaldehyde and benzoic acid. Similarly, aliphatic alcohols are oxidized to aldehydes/ketones, cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Thus, only part of the reaction takes place by one-electron transfer, the remaining ∼40% apparently involving attack by Fe IV aq O 2+ at one of the reactive sites and/or rings in the ABTS molecule causing oxidative degradation. This path is reminiscent of the reaction of the acetonitrile complex Fe IV AN O 2+ with benzyl alcohol and of reactions of other Fe­(IV) complexes with aromatic compounds. , At the low concentrations used, no products could be identified by NMR. The protonated form of the reductant, HABTS – , which is dominant at pH 1 (p K a 2.07) is expected to be unreactive in electron transfer, but it is possible that it engages in a slower side reaction with Fe IV aq O 2+ at the ring.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, only part of the reaction takes place by one-electron transfer, the remaining ∼40% apparently involving attack by Fe IV aq O 2+ at one of the reactive sites and/or rings in the ABTS molecule causing oxidative degradation. This path is reminiscent of the reaction of the acetonitrile complex Fe IV AN O 2+ with benzyl alcohol and of reactions of other Fe­(IV) complexes with aromatic compounds. , At the low concentrations used, no products could be identified by NMR. The protonated form of the reductant, HABTS – , which is dominant at pH 1 (p K a 2.07) is expected to be unreactive in electron transfer, but it is possible that it engages in a slower side reaction with Fe IV aq O 2+ at the ring.…”
Section: Resultsmentioning
confidence: 99%
“…3 b). Today we know for sure that the two-electron oxygenation of ferrous ion by ozone produces such a ferryl species [ 39 43 ].
Fig.
…”
Section: Mechanisms Of C–h Activation By Cytochrome P450s and Other Imentioning
confidence: 99%
“…The decrease in TCE removal indicated that HO• was the dominant species responsible for TCE degradation, but the contribution of other species cannot be neglected as well. Because IPA reacts with Fe(IV) at a very slow rate (3.2×10 3 M −1 s −1 ) compared to HO• (1.9×10 9 M −1 s −1 ) [44], the results of the IPA scavenging tests strongly support the predominant role of HO• rather than Fe(IV) in TCE degradation. Meanwhile, minor inhibition was found in TCE degradation in the presence of CF, though it was much smaller than that of IPA.…”
Section: Resultsmentioning
confidence: 99%